2016
DOI: 10.1038/srep20482
|View full text |Cite
|
Sign up to set email alerts
|

Musical Creativity “Revealed” in Brain Structure: Interplay between Motor, Default Mode and Limbic Networks

Abstract: Creative behaviors are among the most complex that humans engage in, involving not only highly intricate, domain-specific knowledge and skill, but also domain-general processing styles and the affective drive to create. This study presents structural imaging data indicating that musically creative people (as indicated by self-report) have greater cortical surface area or volume in a) regions associated with domain-specific higher-cognitive motor activity and sound processing (dorsal premotor cortex, supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 63 publications
(112 reference statements)
2
42
1
4
Order By: Relevance
“…The left STG is considered to play a key role in integrative processing via selective access to distributed cross-modal representations, which is important in forming novel associations that are required in semantic creativity tasks (Shen et al, 2017). The right MTG has also been implicated in several creativity studies (Bashwiner, Wertz, Flores, & Jung, 2016; Chen et al, 2016; Cousijn, Koolschijn, Zanolie, Kleibeuker, & Crone, 2014; Cousijn, Zanolie, et al, 2014). For example, a recent resting-state study found that divergent thinking ability was related to increased functional connectivity between the right MTG and post-central gyrus (Cousijn, Zanolie, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The left STG is considered to play a key role in integrative processing via selective access to distributed cross-modal representations, which is important in forming novel associations that are required in semantic creativity tasks (Shen et al, 2017). The right MTG has also been implicated in several creativity studies (Bashwiner, Wertz, Flores, & Jung, 2016; Chen et al, 2016; Cousijn, Koolschijn, Zanolie, Kleibeuker, & Crone, 2014; Cousijn, Zanolie, et al, 2014). For example, a recent resting-state study found that divergent thinking ability was related to increased functional connectivity between the right MTG and post-central gyrus (Cousijn, Zanolie, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Each black dot represents a single parcel. Recent studies reported the involvement of DMN regions in narrative comprehension (Simony, Honey, Chen, et al, 2016) and, together with limbic regions, in creative processes (Beaty, Benedek, Silvia, & Schacter, 2017;Shi, Cao, Chen, Zhuang, & Qiu, 2017) as well as in the decoding of emotions conveyed by music (Bashwiner, Wertz, Flores, & Jung, 2016). Higher color intensity indicates higher probability density.…”
Section: The Diversified Organization Of the Dmnmentioning
confidence: 99%
“…Estas áreas destacadas son las siguientes: a) Regiones asociadas con la actividad específica del dominio cognitivo motor y mejor procesamiento de sonido (corteza dorsal premotora y áreas motoras pre-suplementarias y plano temporal); b) Regiones de ideación creativa de dominio general asociadas a la red en modo automático o red por defecto (corteza dorsomedial prefrontal, la circunvolución temporal media y el polo temporal); y c) Regiones relacionadas con las emociones (corteza orbitofrontal, polo temporal y la amígdala) (Bashwiner et al, 2016).…”
Section: La Creatividadunclassified
“…Aunque un estudio actual, ya mencionado anteriormente, señala que personas creativas bajo el dominio musical presentan mayor área de superficie cortical en distintas regiones, entre ellas la asociada con la actividad específica del dominio cognitivo motor y mejor procesamiento del sonido, cuyas áreas son corteza dorsal premotora, áreas motoras suplementarias y plano temporal (Bashwiner et al, 2016).…”
Section: Relación Entre Inteligencias Múltiples Y Creatividad Motrizunclassified
See 1 more Smart Citation